IN VINO VERITAS: AN OVERVIEW OF THE LEGAL ISSUES RELATING TO THE USE OF ALCOHOL IN THE WORKPLACE - Bunn, Anna; Guthrie, Robert (The journal of contemporary issues in business and government, 2010)
According to the Health and Wellbeing Institute of Australia, referring to a 2004/2005 study on the costs of tobacco, alcohol and illicit drug abuse to Australian society, "annual costs of harmful consumption of alcohol are huge with productivity loss in the workplace estimated at $3.5 billion".1 Whilst no industry is exempt from problems related to alcohol consumption amongst its workforce, some industries may be considered to be more at risk than others. The beverage alcohol industry, including the wine industry, is an industry in which certain workers do come into close contact with alcohol: whether at the production or the retail stage. Workers in the wine industry, particularly those involved with harvesting, production and distribution, are often required to operate machinery, vehicles and heavy equipment, work at heights and handle hazardous substances. All of these operations necessitate a workforce whose abilities are not impaired and whose health and safety is not compromised by their consumption of alcohol. One interpretation of data from the National Hospital Morbidity Database estimated that 7.5% of work-related injury cases were alcohol- related2 and other studies have found that there is "sufficient evidence to suggest an association between alcohol use and occupational and machine injuries".3 This is relevant to the wine industry given that a recent infrastructure audit conducted by Wine Australia listed as one of the top five production-related issues for the industry the need to contain occupational health and safety costs and workers’ compensation costs.